43.3k views
0 votes
If k(x) = 5x-6, which expression is equivalent to (k+ k)(4)?

O 5(4+4)-6
O 5(5(4) - 6) -6
054-6 + 54 - 6
O 5(4) - 6 + 5(4) - 6

User Builder
by
5.4k points

2 Answers

5 votes

Answer:D

Explanation:

5(4)-6+5(4)-6

User FloT
by
5.3k points
3 votes

Answer:

  • 5(4) - 6 + 5(4) - 6

Explanation:

Given

  • k(x) = 5x-6

To find

  • (k + k)(4)

Solution

  • (k + k)(x) = 2*k(x) = 2*(5x - 6)
  • (k + k)(4) = 2(5*4 - 6) = 5(4) - 6 + 5(4) - 6

Last option is correct

User Aleli
by
5.7k points